Blastocyst quality and perinatal outcomes of frozen-thawed single blastocyst transfer cycles - Jia, Nan; Hao, Haoying; Zhang, Cuilian; Xie, Juanke; Zhang, Shaodi (Frontiers in Endocrinology, 2022)
Objective: To investigate the effects of blastocyst quality and morphological grade on the perinatal outcomes in patients undergoing frozen-thawed single blastocyst transfer cycles. Methods: This single-center retrospective cohort study included 2648 singleton neonates resulting from frozen-thawed single blastocyst transfers performed between January 2017 and September 2021. Multivariate logistic regression was performed to evaluate perinatal outcomes for their association with blastocyst quality and morphological parameters. Result: Transfer of a good-quality blastocyst in a frozen-thawed cycle was associated with a lower rate of preterm delivery (PTD, adjusted OR =0.7, 95% CI 0.5-0.9; P=0.020) and a higher likelihood of a male neonate (adjusted OR =1.2, 95%CI 1.0-1.5; P=0.048). Compared with grade C inner cell mass (ICM) blastocyst transfer, grade B ICM (adjusted OR =0.5, 95%CI 0.2-0.9; P=0.027) and grade A ICM (adjusted OR =0.6, 95%CI 0.3-1.5; P=0.290) blastocyst transfers were associated with a lower rate of PTD, which was more evident for grade B ICM. After adjusting for confounders, the likelihood of a male neonate (grade B ICM, OR =1.2，95%CI 1.0-1.5, P=0.037; grade A ICM OR =1.9, 95%CI 1.3-28, P=0.002) increased with increasing trophectoderm (TE) quality. Compared with expansion stage 4, the likelihood of a male neonate was 1.5 times greater with transfer of a stage 6 blastocyst (OR =1.5, 95%CI 1.0-2.3; P=0.06), and the risk of small for gestational age (SGA) was greater with transfer of a stage 5 blastocyst (adjusted OR =3.5, 95%CI 1.5-8.0; P=0.004). The overall grading of the blastocyst, expansion stage, ICM grade, and TE grade were not associated with length at birth, birthweight, large for gestational age (LGA), or birth defects (all P>0.05). Conclusions: In frozen-thawed single blastocyst transfer cycles, transfer of a good-quality blastocyst was associated with a lower rate of PTD and a greater likelihood of a male neonate. Transfer of grade B ICM blastocysts decreased the rate of PTD, and TE quality was positively correlated with the likelihood of a male neonate.